Two cases with atypical metastasis in colorectal cancer: splenic and renal metastasis - Dogan, M.; Ozal, G.; Ekinci, C.; Utkan, G.; Urun, Y.; Yalcin, B.; Icli, F. (Experimental Oncology, 2010)
Atypical metastasis, such as splenic and renal metastasis is rare in colorectal cancer. There have been case reports of colorectal cancer patients with isolated splenic metastasis, even after years of surgery in the literature. Aim: To report two colorectal cancer cases with atypical metastasis.